ANALYSIS OF THE IMPACT OF PAYMENT DIGITALIZATION THROUGH QRIS ON THE ECONOMIC RESILIENCE OF MSMES IN MAKASSAR CITY - Wulan Aprilia Utami Putri; Andi Jam'an; Andi Hakib (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the impact of QRIS (Quick Response Code Indonesian Standard) digital payments on the economic resilience of MSMEs in Makassar City, specifically within the Muhammadiyah University of Makassar area. This study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results indicate that QRIS digital payments have a positive impact on the economic resilience of MSMEs, small and medium enterprises (SMEs), through increased operational efficiency, ease of transactions without dependence on cash, automated financial recording, increased sales volume, and expanded market access. With a single QR Code for all digital payment platforms, MSMEs are able to reach more consumers, especially the younger generation. Despite technical challenges, MSMEs are able to adapt well. This study concludes that QRIS functions not only as a digital payment tool but also as a strategic instrument that strengthens poverty reduction, income stability, and economic resilience of MSMEs in Makassar City in facing the dynamics of the digital economy.